Overview of Learning Discipline and Learning Achievement of Students of SMP Negeri 2 Kupang - Dako, Anastasia Zetu; Junias, Marylin Susanti; Panis, Marleny Purnamasari (Universitas Nusa Cendana, 2025)
Abstract. Learning discipline is a collection of individual and community behaviors that reflect a sense of obedience, compliance supported by awareness to fulfill duties and obligations in order to achieve learning goals. Learning discipline applied in the school environment will greatly help in improving student learning achievement. Disciplined behavior is always shown by a student who is always present on time, obeys the rules, behaves in accordance with applicable norms. If a student has been disciplined, namely by obeying the rules of doing all school assignments given to him, it will have a good effect on student learning achievement. This study aims to see the picture of learning discipline and learning achievement of students at SMP Negeri 2 Kupang. This type of research is descriptive quantitative research with the Univariate analysis method, and the number of samples is 97 students. Data was taken using a scale of learning discipline and mid-semester exam scores. Based on the results of the univariate analysis, it shows that the frequency distribution of learning discipline is in the medium category with 65 respondents while learning achievement is in the low category with 44 respondents.